2004
DOI: 10.1111/j.1600-0463.2004.apm11211-1212.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of tools for diagnosis of tularemia and typing of Francisella tularensis

Abstract: Rapid development of molecular techniques for the diagnosis of infections and typing of microbes has been seen during the last 10 years. The present review exemplifies this development by presenting the work of the authors and others regarding techniques for the diagnosis of tularemia and typing of Francisella tularensis. The lack of rapid and safe methods for the laboratory diagnosis of tularemia was the rationale behind the development of methods for the direct detection of F. tularensis in clinical specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 36 publications
3
26
0
13
Order By: Relevance
“…In our cases, MAT test was used for diagnosis. Tularemia is known to be one of the causes of granulomatous lymphadenitis [1][2][3]21] , and histopathological findings supported the diagnosis in one of our cases.…”
Section: /205supporting
confidence: 73%
See 1 more Smart Citation
“…In our cases, MAT test was used for diagnosis. Tularemia is known to be one of the causes of granulomatous lymphadenitis [1][2][3]21] , and histopathological findings supported the diagnosis in one of our cases.…”
Section: /205supporting
confidence: 73%
“…Helvaci et al [13] reported that bacteria were isolated in five seronegative cases. A definite diagnosis of tularemia is established by isolating the agent from body samples such as lymph nodes, wounds, sputum, blood, and pleural fluid [1,3,17,20,21] . However, due to the high virulence and contagiousness of the microorganism, culture is not recommended unless the necessary safety precautions are taken.…”
Section: /205mentioning
confidence: 99%
“…If several typing methods, such as Insertion Sequence Probed RFLP (Thomas et al 2003), macrorestriction using pulsed field gel electrophoresis (PFGE) and amplified fragment length polymorphism (Garcia Del Blanco et al 2002), repetitive element PCR, arbitrarily primed PCR (Johansson et al 2000), and ribotyping (Grif et al 2003) were eventually used for typing F. tularensis subspecies, the results would lack high-resolution discrimination between individual strains. Multilocus sequence typing (MLST) failed to separate F. tularensis strains at the strain level (Johansson et al 2004b). Techniques based on the analysis of variablenumber tandem repeats identified F. tularensis at the strain level and also identified epidemic strains (Farlow et al 2001;Johansson et al 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…The primer concentration was . The cycling programme was as described by Johansson et al [11]. Three microlitres of the PCR products were mixed with an equal volume of loading buffer (99 .…”
mentioning
confidence: 99%